1999
DOI: 10.1111/j.1600-0404.1999.tb07347.x
|View full text |Cite
|
Sign up to set email alerts
|

Compression of the visual pathway by anterior cerebral artery aneurysm

Abstract: Visual failure is an uncommon presenting symptom of an intracranial aneurysm. It is even more uncommon in aneurysms arising from the anterior cerebral artery (ACA). We presented 2 patients with an aneurysm of the A1 segment of the anterior cerebral artery causing visual field defects. One patient presented with a complete homonymous hemianopia due to compression of the optic tract by a giant aneurysm of the proximal left A1 segment. The second patient had an almost complete unilateral anopia caused by compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…7 Nevertheless, several studies have reported aneurysms in any portion of the circle of Willis producing compression over the visual pathways. 3,6,7,11,15 Although paraclinoidal aneurysms represent only 5% of intracranial aneurysms, they are the most common cause of visual complaints caused by aneurysmal compression of the ON and chiasm. 8 In this study, paraclinoidal (in 8 patients) and ACoA (in 5 patients) aneurysms also represented the majority of the cases (86.6%).…”
Section: Aneurysms Characteristics and Patterns Of Visual Field Lossmentioning
confidence: 99%
“…7 Nevertheless, several studies have reported aneurysms in any portion of the circle of Willis producing compression over the visual pathways. 3,6,7,11,15 Although paraclinoidal aneurysms represent only 5% of intracranial aneurysms, they are the most common cause of visual complaints caused by aneurysmal compression of the ON and chiasm. 8 In this study, paraclinoidal (in 8 patients) and ACoA (in 5 patients) aneurysms also represented the majority of the cases (86.6%).…”
Section: Aneurysms Characteristics and Patterns Of Visual Field Lossmentioning
confidence: 99%
“…Cases of acute visual loss caused by cerebral aneurysms have been reported previously in the literature. Anterior communicating artery (ACoA) rupture,[726] ACoA aneurysm enlargement,[3] anterior cerebral artery (ACA) aneurysm rupture,[2] carotid-ophthalmic aneurysm enlargement,[11] and mycotic cavernous pseudoaneurysm enlargement[19] have resulted in sudden monocular blindness. Carotid dissection has also caused sudden monocular loss of vision.…”
Section: Discussionmentioning
confidence: 99%
“…Optic chiasmal syndrome can be caused by a variety of lesions, in-cluding tumors and carotid artery aneurysms 1 ; however, reports of bitemporal field loss from compression by an abnormal vessel are rare. 2 We describe a patient with a nonprogressive bitemporal hemianopia in whom there appeared to be compression of the optic chiasm by an elongated right anterior cerebral artery (ACA).…”
Section: Bitemporal Hemianopia Caused By An Intracranial Vascular Loopmentioning
confidence: 99%
“…Vascular compression of the optic chiasm causing a bitemporal field defect is most often due to an aneurysm of the ACA, internal carotid artery, or anterior communicating artery. 1 Rare cases of dolichoectatic and atherosclerotic ACAs that cause bitemporal hemianopia have been reported, but direct chiasmal i m p i n g e m e n t h a s n o t b e e n described. The field defect in such cases is thought to result from traction on small perforating vessels causing a chiasmal infarction.…”
Section: Bitemporal Hemianopia Caused By An Intracranial Vascular Loopmentioning
confidence: 99%